Analisis Posisi Indonesia Sebagai Eksportir Lada di Pasar Internasional - Budiarto, Fadia Nur Rahma; Sri TJondro Winarno; Prasmita Dian Wijayati (Hasanuddin University, 2024)
Indonesia is one of the world's producers of pepper. Indonesia also ranks sixth as a pepper exporter in the international market. From 2013 to 2022, Indonesia's pepper exports have been continuously declining, threatening Indonesia's position as a global pepper exporter. Objectives. This research analyzes Indonesia's position as a pepper exporter in the international market, as well as a comparison with competing countries. Method. The method used is the Trade Specialization Index (TSI) and Revealed Comparative Advantage (RCA), with Vietnam and India as the comparison countries. Results. The results of the study show that Indonesia has not been able to compete with Vietnam and India, but it has positive TSI and RCA value, indicating that Indonesia possesses competitive and growing export potential.